Innovation-Led Economy Aspiration by Year 2020: Are Malaysian Universities Ready? - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2013)
Throughout East Asia, the urgency of nurturing innovation oriented human capital is pressing. In Malaysia, the government policy has been shifted from resources based to innovation-led economy. Malaysia government believe that innovation-led economy will enable Malaysia to achieve high income status by the year 2020. Their believed is that innovation will boost new values creation in term of new product and service thus creates competitive edges in the market competition for Malaysia.